The plica syndrome in the knee: a histopathological pilot study - Grevenstein, David; Mamilos, Andreas; Schmitt, Volker H.; Babel, Maximilian; Rupp, Markus; Winter, Lina; Brochhausen, Christoph (Pathology, research and practice, 2025)
The plica syndrome, a condition caused by hypertrophy of the medial plica in the knee, is clinically characterized by antero-medial knee pain, especially in sport activities involving repetitive joint extension and flexion. Despite its high prevalence in young individuals, it is often overlooked, and there is a lack of systematic examination regarding characteristic histopathological changes associated with this syndrome. We performed a retrospective histological evaluation using haematoxylin-eosin, Elastica van Gieson and Berlin-blue staining and correlated clinical data of 45 plicae obtained from patients diagnosed with symptomatic plica syndrome. Our analysis focused on identifying characteristic pathological changes, especially acute and chronic inflammatory signs. The majority of examined plicae showed signs of fibrosis. Chronic inflammatory reactions dominated over acute inflammatory reactions. Additionally, hypertrophy of the synovial covering cells was observed. Lymphocyte aggregation occurred, while bleeding and fatty tissue reorganisation were rare. Our findings suggest that inflammation plays an active role in the development and maintenance of the plica syndrome. Future studies should prioritize the development of a histopathological scoring system for plica syndrome and the question whether the plica syndrome represents a risk factor for osteoarthritis.
Online verfügbar: 28. Juli 2025, Artikelversion: 30. Juli 2025
Gesehen am 08.01.2026